Optimasi Asam Glikolat dan Asam Sitrat dalam Krim Tabir Surya Kombinasi Titanium Dioksida, Avobenzone dan Octyl Methoxycinnamate - desy diana sari; Lidya Ameliana; Dwi Nurahmanto (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Ultraviolet (UV) radiation is the main cause of sunburn and skin cancer. The adverse effects of UV radiation are solved by sunscreen as protection for longer outdoors. In this study, optimization of glycolic acid and citric acid in sunscreen cream combination of titanium dioxide, avobenzone, and octyl methoxycinnamate were investigated using simplex lattice design method. The sunscreen cream evaluation includes physicochemical testing (organoleptic, homogeneity, emulsion type, spreadability, viscosity, and pH) and sunscreen effectiveness (SPF, % erythema transmission, and % pigmentation transmission). The value of physicochemical testing are 5,96 cm - 6,3 cm of spreadability testing; 83,33 dPa.s – 108,33 dPa.s of viscosity testing; 4,06 – 4,67 of pH testing. The value of sunscreen effectiveness are 9,79 – 13,35 of SPF testing; 4,55x10-06 - 0,15x10-06% of % erythema transmission; 5,77 – 7,16 % of % pigmentation transmission. The optimum formula was obtained by combining glycolic acid 2% and citric acid 0% with a desirability value of 0,649.